2018
DOI: 10.1126/science.aar3247
|View full text |Cite
|
Sign up to set email alerts
|

Detection and localization of surgically resectable cancers with a multi-analyte blood test

Abstract: Earlier detection is key to reducing cancer deaths. Here, we describe a blood test that can detect eight common cancer types through assessment of the levels of circulating proteins and mutations in cell-free DNA. We applied this test, called CancerSEEK, to 1005 patients with nonmetastatic, clinically detected cancers of the ovary, liver, stomach, pancreas, esophagus, colorectum, lung, or breast. CancerSEEK tests were positive in a median of 70% of the eight cancer types. The sensitivities ranged from 69 to 98… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

38
1,771
4
20

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,120 publications
(1,965 citation statements)
references
References 37 publications
38
1,771
4
20
Order By: Relevance
“…However, depending on the tumour type the detection rates ranged between 30% and 95%. Particularly in early stage tumours, the detection rate of about 40% was only limited [10].…”
mentioning
confidence: 99%
“…However, depending on the tumour type the detection rates ranged between 30% and 95%. Particularly in early stage tumours, the detection rate of about 40% was only limited [10].…”
mentioning
confidence: 99%
“…Studies have suggested its potential for early cancer detection and cancer recurrence prediction. In a translational study by Cohen etal ., the combination of several biomarkers including ctDNA analysis provided sensitivities ranging from 69 to 98 for five different cancer types with specificity greater than 99 [3]. However, similar to CTCs, ctDNA exists in trace amounts, from less than 0.1 to more than 10 of the total circulating free DNA [4].…”
mentioning
confidence: 99%
“…4 The last approximation cancer SEEK, which combine genetic markers and protein markers for detection up to five different types of cancer (ovary, liver, stomach, pancreas and esophagus), and estimate the origin of tumor cells in a significant proportion of cases. 5 Additionally, have been studied miRNA, markers with better capacity to predict cancer than DNA or mRNA since a single molecule of miRNA has the capacity to regulate more than one hundred mRNA, with which they have orders of magnitude much greater in terms of the information about the prognosis that they provide us. Currently different molecular biology tools had permitted to develop molecular tumor signatures based on mRNA , miRNA and DNA 6 that can help in tumor classification, subtype and ability to respond to certain therapies nowadays several of these are used in clinical practice.…”
mentioning
confidence: 99%